Critical analysis of separatist feminism from the Qur’anic perspective - Ahmad, Nadzrah; Ishak, Mohd Haeqal; Ghazali, Norzulaili; Aminudin, Rabi'ah (Global Academic Excellence, 2017)
Separatist feminism is a controversial issue even in feminism stream. Its objective and radical approach for women liberation brings lot of criticism from scholars all around the globe. Nevertheless, this ideology is gaining influence day by day. This study will focus on the ideology of separatist feminism and analyse it from the Qur’anic perspective. This study aims to broaden the scope of understanding of this particular feminism branch; its characteristics and issues, and how the Quran views it especially on the aspect of women rights and liberation. It is a qualitative study that utilizes the deductive and inductive method. Separatist feminism works and critics will be examined in the light of in the Qur’anic understanding and the result indicates that there are several characteristic and issues of separatist feminism that can propagates better understanding on feminism as a whole.